THE INFLUENCE OF GOOD CORPORATE GOVERNANCE ON COMPANY PERFORMANCE WITH CORPORATE SOCIAL RESPONSIBILITY AS A MODERATING VARIABLE - Jeffry Sinaulan; Sri Sugiarti; Shofia Asri (Adisam Publisher, 2025)
This research is a quantitative study with an explanatory approach, namely an approach that uses a number of previous studies as the main foothold in proving the formulated hypothesis, namely that the Good Corporate Governance variable can affect Company Performance and the Corporate Social Responsibility variable can moderate the effect of the Good Corporate Governance variable on Company Performance. The data used in this article is primary data that researchers obtained from DAMRI employees throughout Indonesia. The data used was analyzed using the smart PLS 4.0 analysis tool